1984
DOI: 10.1002/jez.1402320207
|View full text |Cite
|
Sign up to set email alerts
|

On the role of fibronectin during the compaction stage of somitogenesis in the chick embryo

Abstract: During the early stages of somitogenesis in the chick embryo the presomitic cells in the segmental plate undergo compaction. The aggregation of segmental plate cells is stimulated by fibronectin. The stimulation of segmental plate cells to aggregate and undergo compaction can be effected in isolated segmental plate cells, in isolated segmental plates, and in intact embryos removed from the yolk. The fact that the segmental plate cells react with greater vigor to cellular fibronectin than to plasma fibronectin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 13 publications
0
27
0
2
Order By: Relevance
“…Only the more mature segmental plate cells react to the peptide. This suggestion is supported by the finding of an antero-posterior diminishing gradient of fibronectin along the segmental plate (Ostrovsky et al, 1983;Lash et al, 1984) and an increase in cell-cell adhesion between the anterior segmental plate cells (Bellairs et al, 1978;Cheney and Lash, 1984). Further evidence for anterior-posterior differences was reported by George-Weinstein et al (1994) who found that segmental plate cells undergo an increasing ability to differentiate with a n increased residence time in the mesodermal layer after gastrulation.…”
Section: Discussionmentioning
confidence: 90%
“…Only the more mature segmental plate cells react to the peptide. This suggestion is supported by the finding of an antero-posterior diminishing gradient of fibronectin along the segmental plate (Ostrovsky et al, 1983;Lash et al, 1984) and an increase in cell-cell adhesion between the anterior segmental plate cells (Bellairs et al, 1978;Cheney and Lash, 1984). Further evidence for anterior-posterior differences was reported by George-Weinstein et al (1994) who found that segmental plate cells undergo an increasing ability to differentiate with a n increased residence time in the mesodermal layer after gastrulation.…”
Section: Discussionmentioning
confidence: 90%
“…46 Somitogenesis in the chick embryo also involves an FN-dependent event in which presomitic cells in the segmental plate undergo compaction. 47 Thus, strong tissue cohesion can be brought about not only through direct cell-cell interactions, as mediated by cadherins, but also indirectly via integrin-ECM interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of somites is obviously dependent on increased cell adhesion between the cells at the rostral end of the presomitic mesoderm as compared to cells located further caudally (Bellairs et al, 1978;Cheney and Lash, 1984;Lash et al, 1984). It has been shown that the expression of both the calcium-dependent adhesion molecule N-cadherin, and the neural cell adhesion molecule (NCAM), is upregulated just before somite formation (Hall and Miyake, 1992).…”
Section: B Cell Adhesion-mentioning
confidence: 99%
“…Components-Fibronectin is a major component of the extracellular matrix and long been implicated in the epithelialization of somites Lash et al, 1984). For example, addition of fibronectin or a peptide corresponding to the cellular recognition site of fibronectin can stimulate aggregation of disaggregated paraxial mesoderm cells in vitro Lash et al, 1984).…”
Section: C Extracellular Matrixmentioning
confidence: 99%
See 1 more Smart Citation